Urine NGAL and KIM-1—Tubular Injury Biomarkers in Long-Term Survivors of Childhood Solid Tumors: A Cross-Sectional Study - Latoch, Eryk (J Clin Med, 2021)
The deterioration of renal function after childhood solid tumors treatment is the result of using the intensive multimodal therapy. In recent years, urinary kidney injury molecule-1 (KIM-1) and urinary neutrophil gelatinase-associated lipocalin (NGAL) have been introduced as potential promising biomarkers of early kidney damage. The aim of the present study was to determine whether anticancer treatment has any effect on the concentration of KIM-1 and NGAL and its association with renal impairment in survivors of childhood solid tumors. Sixty patients previously treated for solid tumors were involved in this study. The median time after end of treatment was 8.35 years. Urine KIM-1 and NGAL levels were measured using immunoenzymatic ELISA commercial kits. Higher levels of urine NGAL, KIM-1/cr. (creatinine), and NGAL/cr. ratios were found in comparison with healthy controls (p < 0.0001). Among all subjects, 23% were found to have decreased estimated glomerular filtration rate (eGFR). A strong correlation between KIM-1/cr. and a cumulative dose of ifosfamide was observed (r = 0.865, p < 0.05). In addition, a moderate correlation between NGAL/cr. and a cumulative dose of cisplatin was identified (r = 0.534, p < 0.05). The AUC for KIM-1/cr. was 0.52, whereas NGAL/cr. showed a diagnostic profile describing the AUC of 0.67. Univariable regression showed significant associations between NGAL/cr. ratio and subjects after unilateral nephrectomy (coeff. 63.8, p = 0.007), cumulative dose of cisplatin (coeff. 0.111, p = 0.033), and age at diagnosis (coeff. 3.75, p = 0.023). The multivariable model demonstrated only cumulative dose of cisplatin as an independent factor influence on NGAL/cr. ratio. The results of our study showed increased levels of urine KIM-1 and NGAL many years after completion of the childhood solid tumors treatment, which correlated positively with a cumulative dose of ifosfamide and cisplatin. This study also suggests that unilateral nephrectomy could affect the concentration of the studied biomarkers.